Reverse Pharmacological Approach: A Narrative Review - Prerana Sakharwade (International Journal of Medical Toxicology and Legal Medicine, 2024)
The situation of drug research and development today is unsurmountable, notwithstanding notable advancements in high throughput tests. New approaches to medication research are therefore desperately needed. Almost 70% of Indians used Ayurveda. It is time to change the way that native plants are systematically and empirically searched for their potential health benefits. Reverse pharmacological techniques, observational studies, and Ayurvedic epidemiology have yielded impressive results, indicators, as well as parts for a variety of of illnesses and ailments. Potential frameworks to medicinal chemists to increase efficacy while reducing toxicity will include the possible phytobase entity. Numerous indigenous medicinal herbs have demonstrated efficacy. Reverse pharmacology uses conventional drugs with a track record of therapeutic action as a springboard for new drug discovery. On the other hand, known natural product medications from conventional medicine are typically blends of substances with various pharmacological effects. Because of the intricate interplay between the components’ pharmacological effects and the traditional drug’s overall pharmacological effects, it is very challenging to determine which of its active ingredients they are and to understand their mechanisms of action. The main concept utilised to solve this issue is that approaches to drug development that are influenced by traditional medicine should begin with the significance of determining the content foundation for the effectiveness and elucidating the way that pharmacology works in conventional drugs. Many organisations employ reverse pharmacology worldwide to create new compounds, formulations, and baits for drugs.